Effect Of Variation In Volume Addition Of Tofu Waste To Rice Straw On Biogas Formation - Silda Pacitra; Karyanik Karyanik; Sirajuddin H. Abdullah; Earlyna Sinthia Dewi (Universitas Muhammadiyah Mataram, 2024)
Abstract: Biogas is a renewable energy source. Biogas can be produced from agricultural waste and industrial waste. One of the alternatives to handling tofu industry waste that currently has a lot to be developed is to convert industrial waste into alternative fuel in the form of biogas. This study aims to determine the effect of the addition of tofu liquid waste on changes in temperature, pH, volume and pressure that occur during the formation of biogas. This research was conducted from July to August for 22 days. The method used in this research is the experimental method by conducting direct experiments. The design used in this study was a one-factor Completely Randomised Design (CRD), consisting of P0 with rice straw + 4 litres of water, P1 with the addition of 20% tofu liquid waste, P2 with 40%, P3 with 60%, P4 with 80% and P5 with 100%. Observation data were analysed with Analysis of Variance at the 5% level. The parameters observed in the study were temperature, pH, volume and pressure. Based on the results of the analysis that has been done, the lowest temperature was obtained in the P3 treatment at 27.39 ° C, while the highest temperature was obtained in the P2 treatment at 27.86 ° C. The lowest pH was obtained in the P5 treatment at 4.24, while the highest pH was obtained in the P1 treatment at 4.57. The lowest volume was obtained in the P1 treatment at 0.00000011513 m3, while the highest volume was obtained in the P0 treatment at 0.00000161291m3, the lowest pressure was obtained in the P3 treatment at 109.08 N/m2, while the highest pressure was obtained in the P2 treatment at 109.25 N/m2. Therefore, it can be concluded that the addition of tofu waste to rice straw does not significantly affect the formation of biogas produced.